URGENSITAS PENDIDIKAN AKHLAK BAGI ANAK USIA DASAR (Studi Era Darurat Covid 19) - Muhammad Shaleh Assingkily; Miswar Rangkuti (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Morals that “color” the environment. Every period, including the era of “emergency Covid-19”, is needed to cultivate morals for elementary age children as a continuation of the “khalifah on earth” relay. This paper examines the urgency of moral cultivation for children of primary age in the era of disruption. The research problem formulation is focused on how the efforts and urgency of moral cultivation for elementary age children in the era of “emergency Covid-19”. This research uses a qualitative approach with the literature study method. The results of this study indicate that the cultivation of morals is an urgent matter that should be given from elementary age to children. This is marked by efforts to meet the demands of the times with 4 (four) aspects, namely (1) education upgrading the quality of the curriculum, (2) providing internalization of values, (3) raising awareness of changing times, and (4) bringing students find self concept.Keywords: Morals, Elementary Children, Disruptive Era.